Sourdough technology as a tool for the development of healthier grain-based products: An update - Fernández Peláez, Juan (2020)
There has been growing demand by consumers for grain-based products with well-balanced nutritional profiles and health-promoting properties. The components of the flours obtained from different grains can be modified or improved at a nutritional level by using sourdough technology, which has gained increasing interest in recent years. Sourdough hydrolyse dietary fibre, reduces fat rancidity, and enables an increase in starch and protein digestibility, as well as vitamin levels and mineral bioavailability. In addition, bioactive compounds are synthesized during fermentation, while components that interfere with the digestion of grain-based products or digestion-linked pathologies, such as gluten sensitivity or gastrointestinal syndromes, are reduced. Finally, it has been observed that sourdough fermented products can play a role in gut microbiota regulation. Thanks to this health-promoting potential, sourdough can stand out among other fermentation processes and opens up a new range of healthier commercial products to be developed. The current review discusses the extensive research carried out in the last 15 years and aims at updating and deepening understanding on how sourdough can enhance the nutritional and health-related characteristics of the different components present in the grains.